Dynamics of structural transformation: An empirical characterization in the case of China, Malaysia, and Ghana - Badibanga, Thaddée; Diao, Xinshen; Roe, Terry L.; Somwaru, Agapi (International Food Policy Research Institute, 2009)
The paper develops a metric of structural transformation that can account for the production of new varieties of goods embodying advancements in technological know-how and design. Our measure captures the dynamics of an economy's transformation and can be viewed as an extension of Hausmann and Klinger's static measure. We apply our measure to four-digit-level SITC trade data of China, Malaysia, and Ghana over the period 1962-2000. The results show that two important factors characterize the rapid transformation of the Chinese economy: the high proximity of its export basket to three main industrial clusters-capital goods, consumer durable goods, and intermediate inputs-and the increase in the values of the new goods belonging to those three clusters. Malaysia exhibits a similar but more modest pattern. In contrast, the structure of the Ghanaian economy appears unchanged over the entire 1962-2000 period. That economy is dominated by primary goods clusters, and the values of the goods in those clusters have remained relatively low. We also discuss qualitatively the role of policies and institutions in spurring transformation in the three countries.